Transformer model with saturation effects for frequency‐domain transients simulation. Issue 1 (1st January 2017) - Luna, Carlos M.; Moreno, Pablo; Loo‐Yau, José Raul
Abstract : In this study, a model of one‐phase transformers with saturation effects, suitable for low‐ and mid‐frequency electromagnetic transient simulations using the numerical Laplace transform is presented. Substitution and superposition theorems are invoked to convert the saturation non‐linear condition of the transformer into a series of time‐sequential switching manoeuvres. Model advantage is that frequency dependence of electrical parameters is naturally taken into account and, together with the capability of including non‐linear phenomena, leads to a valuable tool to validate time‐domain models based on convolutions.